Masons and the People: A Study of political sociability in Colombia, 1850-1873 - Rubio, Juana M. (Pontificia Universidad Javeriana, 2014)
In 1862, Tomás Cipriano de Mosquera decreed a schism  within the Masonic Order, which legitimized the political project of this group that was developed in the context of the middle of the nineteenth century in Colombia. This article will explain this project from its intellectual base demonstrating the relationship between a society of secret and exclusive ideas with the application of the social policies that would benefit the ruling liberal elite.